Directional Emission from Tungsten Disulfide Monolayer Coupled to Plasmonic Nanowire‐on‐Mirror Cavity. Issue 6 (6th May 2021) - Chaubey, Shailendra K.; A, Gokul M.; Paul, Diptabrata; Tiwari, Sunny; Rahman, Atikur; Kumar, G. V. Pavan
Abstract : Influencing spectral and directional features of exciton emission characteristics from 2D transition metal dichalcogenides by coupling it to plasmonic nanocavities has emerged as an important prospect in nanophotonics of 2D materials. Herein, the directional photoluminescence emission from a tungsten disulfide (WS2 ) monolayer sandwiched between a single‐crystalline plasmonic silver nanowire (AgNW) waveguide and a gold (Au) mirror is experimentally studied, thus forming a AgNW–WS2 –Au cavity. Using polarization‐resolved Fourier‐plane optical microscopy, the directional emission characteristics from the distal end of the AgNW–WS2 –Au cavity are quantified. Given that the geometry simultaneously facilitates local field enhancement and waveguiding capability, its utility in 2D material‐based, on‐chip nanophotonic signal processing is envisaged, including nonlinear and quantum optical regimes. Abstract : Wavevector distribution of the photoluminescence (PL) from a monolayer tungsten disulfide (WS2 ) is studied by sandwiching it in Ag nanowire (NW)–gold mirror cavity. This cavity works as a subdiffraction waveguide for WS2 PL. A Fourier‐plane image of the distal end of the NW exhibits directional emission when analyzed for the polarization along the long axis of the NW.